Thyroid Autoimmunity and Reproductive Function - Crawford, Natalie M.; Steiner, Anne Z. (Seminars in Reproductive Medicine, 2016)
Thyroid hormones are important for normal reproductive function, and maternal thyroid dysfunction has been associated with infertility, miscarriage, preterm birth, and poor neurodevelopment in the offspring. Thyroid autoimmunity is the leading cause of thyroid dysfunction in women of reproductive age. Women with thyroid autoimmunity, even with normal thyroid function, appear to be at a higher risk for poor reproductive outcomes, including miscarriage and preterm birth. Thyroxine replacement in women with thyroid autoimmunity with or without appreciable thyroid dysfunction may improve pregnancy outcomes. Thus, identification and treatment of women with thyroid autoimmunity may optimize reproductive success.
Keywords: thyroid autoimmunity; hypothyroidism; infertility; miscarriage; pregnancy